Permasalahan Penggunaan Google Classroom pada Pengajaran Pendidikan Agama Islam di Sekolah Dasar - Nasikhin Nasikhin; Raharjo Raharjo; Nasikhin Nasikhin; Ismutik Ismutik; Ulul Albab (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: The focus of this research is to find out the responses of students and teachers in using Google Classroom in Islamic religious education lessons in elementary schools during online learning. A qualitative approach with the QAIT model is used as an effort to evaluate the ability of Google Classroom in teaching Islamic Religious Education. This study involved 4 teachers and 15 students of SD Islam Al-Azhar 29 Semarang. Data were collected through observation of teaching and learning process activities in the classroom. The results showed: (1) the use of Google Classroom can be utilized well by young teachers (aged 21 and 34 years), teachers whose performance is quite good are in the age range of 43 years, and teachers whose performance is less than 50 years old; (2) this study shows that the obstacles found in the learning process are poor internet connection, lack of supportive learning tools, low learning motivation, and lack of readiness to use online learning platforms. This research is useful for determining the direction of religious education policies, such as the need for training in using Google Classroom to improve the quality of better online learning. Abstrak: Fokus penelitian ini adalah mengetahui respon siswa dan guru dalam menggunakan Google Classroom pada pelajaran pendidikan agama Islam di Sekolah Dasar selama pembelajaran online. Pendekatan kualitatif dengan Model QAIT digunakan sebagai upaya untuk mengevaluasi kemampuan Google Classroom dalam pengajaran Pendidikan Agama Islam. Penelitian ini melibatkan 4 guru dan 15 siswa SD Islam Al-Azhar 29 Semarang. Data dikumpulkan melalui observasi terhadap kegiatan proses belajar mengajar di kelas. Hasil penelitian menunjukkan: (1) penggunaan Google Classroom dapat dimanfaatkan dengan baik oleh guru berusia muda (Usia 21 dan 34 tahun), guru yang kinerjanya cukup baik berada pada rentang usia 43 tahun, dan guru yang kinerjanya kurang berada pada usia 50 tahun; (2) penelitian ini meperlihatkan bahwa kendala yang ditemukan dalam proses pembelajaran adalah koneksi internet yang buruk, kurangnya perangkat pembelajaran yang mendukung, motivasi belajar yang rendah, dan kurangnya kesiapan dalam menggunakan platform pembelajaran online. Penelitian ini bermanfaat untuk menentukan arah kebijakan pendidikan agama, seperti diperlukannya pelatihan dalam menggunakan Google Classroom untuk meningkatkan kualitas pembelajaran online yang lebih baik.